A NEEDS ANALYSIS OF CHINESE LANGUAGE TEACHING MATERIALS FOR STUDENTS OF BUSINESS AND MANAGEMENT MAJORS IN A VOCATIONAL HIGH SCHOOL - Ayu Fitria; Yumna Rasyid; Ninuk Lustyantie (Polyglot, 2019)
The purpose of this study was to identify the Chinese language teaching materials for students of business and management majors in a vocational high school. This research method was qualitative. The process of collecting data used observation activities, interviews and questionnaires. This study found that the Chinese teaching materials which have been used in a vocational high school especially in business and management majors were still general and not relevant to the needs of students. The results of this study also indicated that the expected design of Chinese language teaching materials should be specifically integrated to the students’ majors and the competency levels of their expertise. In addition, the teaching materials also should be designed with multimedia to support the learning process and students’ experiences.BAHASA INDONESIA ABSTRAK: Penelitian ini bertujuan untuk mengidentifikasi kebutuhan model materi ajar bahasa Mandarin untuk Sekolah Menengah Kejuruan Bidang Bisnis dan Manajemen. Penelitian ini merupakan penelitian kualitatif dengan proses pengumpulan data melalui observasi, wawancara dan kuesioner. Melalui penelitian ini ditemukan bahwa materi ajar bahasa Mandarin yang selama ini digunakan di Sekolah Menengah Kejuruan Bidang Bisnis dan Manajemen merupakan materi ajar yang bersifat umum dan belum memenuhi kebutuhan siswa. Hasil dari analisis kebutuhan menunjukkan bahwa materi ajar bahasa Mandarin yang diharapkan adalah materi ajar yang terintegrasi dan relevan dengan bidang dan program studi siswa sehingga dapat mendukung keahlian utamanya. Terlebih lagi materi ajar bahasa Mandarin yang diharapkan saat ini adalah materi ajar yang dikemas dengan basis multimedia.